Liberalisasi Islam Di Indonesia Perspektif Kontektual - Jejen Kurnia Azri (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2017)
This study tries to analyze Islamic Liberal thought in Indonesia context. Islamic Liberal in this study analyzed of its genealogy, a frame of reference and contextuality of issue on Indonesia, by using two approaches were complementary. The first, by using positivistic approach to objective explanation an Islamic Liberal thought. The second, by using verstehen approach to interpret the meaning of Islamic Liberal thought on its context. It‟s found that in Islamic Liberal thought there are many problems that can make social destruction, because it goes beyond text, seeking that which is represented or revealed by language, then it‟s miss social meaning which based on the text. Islamic Liberal thought didn‟ really destructive in it‟s thought, but in its implementation which is not true to context. In the middle east context, Islamic Liberal thought struggles to liberate the spirit of Islam from corrupt power isolation. But isn‟t like that on Indonesia, because the political majority in Indonesia isn‟t majority religious.